Internet of Things (IoT) Innovation Solution for Making Biomass Stoves in Padasuka Village, East Sumedang - Haris Supriatna; Win Hendrawan; Feri Alpiyasin; Ahfi Fauka Pranata; Rizal Parghani (LPPM STMIK Mardira Indonesia, 2024)
The community service team, comprising instructors and students from STMIK Mardira, in partnership with Universitas Kebangsaan Republik Indonesia, initiated an initiative to develop Sukajadi Village in East Sumedang. During the project, the team concentrated on resolving the challenge of biomass stoves utilizing the Internet of Things (IoT) with temperature sensors capable of real-time temperature monitoring and remote temperature control. The team ensured a consistent temperature of 90°C during the steaming process to preserve the quality and sterility of East Mushroom spawn bags. The community service team implemented IoT-based biomass stoves and conducted training for the local population in Padasuka Village to optimize the use of these stoves for temperature monitoring. The community service project resulted in the deployment of IoT-enabled biomass burners for real-time temperature monitoring during the steaming of oyster mushroom bags for the inhabitants of Padasuka Village in East Sumedang. The IoT-enabled biomass burners allow the local community to monitor the temperature in real-time, as shown on the application screen, to maintain a consistent temperature of 90°C for optimal steaming processes. The collaborative community project in Sukajadi Village has substantially benefited the local community by adopting IoT-based technology for real-time temperature monitoring of biomass burners. The measures implemented are anticipated to be further improved and yield enduring advantages for the inhabitants of Sukajadi Village in East Sumedang.